171k views
2 votes
Help me solve this problem please

Help me solve this problem please-example-1
User Rsanchez
by
5.8k points

2 Answers

4 votes

Answer:

(2, -2)

Explanation:

4x + y = 6

x - 2y = 6

x = 2y + 6

4(2y + 6) + y = 6

8y + 24 + y = 6

9y + 24 = 6

9y = 6 - 24

9y = -18

y = -18 ÷ 9

y = -2

4x + (-2) = 6

4x - 2 = 6

4x = 6 + 2

4x = 8

x = 8 ÷ 4

x = 2

Confirm:

4x + y = 6

4(2) - 2 = 6

8 - 2 = 6

6 = 6 (Correct)

(2, -2)

User Frady
by
5.2k points
7 votes

Answer: (2, -2)

x=2, y=-2

User Timsabat
by
5.3k points